تقييم إمكانية قلع الرحى الثالثة العلوية المنطمرة بحقن الأرتيكائين هيدروكلوريد في الجهة الشدقية فقط - خليل, عبد الكريم; شهيرة, بشار (Latakia University Journal -Medical Sciences Series, 2019)
أجريت هذه الدراسة السريرية لتقييم فيما إذا كان استخدام الأرتيكائين%4 مع الإبينفرين 1:100,000 كحقنة ارتشاحية شدقيه وحيدة في قلع الرحى الثالثة العلوية المنطمرة يؤمن تخديراً حنكياً ملائماً مقارنة بالحقن الشدقي والحنكي التقليدي المستخدم للإجراء الجراحي ذاته. تم اختيار 90 سناً لـ 45 مريضاً لإدراجهم في الدراسة الحالية. وبهدف اجراء المقارنة، تم تقسيم العينة بطريقة عشوائية إلى مجموعتين رئيسيتين: المجموعة الأولى I (مجموعة الدراسة) وتضمنت 30مريضاً ممن سيتلقون حقنة شدقيه مفردة بهدف رفع 60 رحى ثالثة علوية ثنائية الجانب. أما المجموعة الثانية II (المجموعة الشاهدة) فتضمنت 15 مريضاً ممن سيتلقون حقنتي التخدير الشدقيه والحنكية التقليدية. كما قسم المرضى في المجموعة I إلى تحت مجموعتين (A) و (B). تم تخدير المرضى في المجموعة (A) باستخدام أرتيكائين 4% مع ابنيفرين 1:100k وتم اجراء القلع بعد ست (6) دقائق من اجراء التخدير. واستخدم نفس المحلول المخدر عند المجموعة (B) ولكن تم الانتظار اثنا عشر (12) دقيقة من أجل انتشار المخدر قبل مباشرة القلع. تم تسجيل المعلومات التالية: الألم في أثناء ادخال الإبرة وترسيب المحلول، معدلات الألم خلال مختلف مراحل الجراحة لكلتا المجموعتين بالأرقام، والنسب المئوية للقلوع التي أنجزت بدون ومع تخدير حنكي إضافي. كان معدل كفاية الارتشاح الشدقي- الحنكي والذي حدّد بناءً على عدم الحاجة لتخدير حنكي إضافي (73.7%) للمجموعة A، و (90.2%) للمجموعة B. معظم القلوع الجراحية يمكن إنجازها بتخدير شدقي فقط. مع ذلك فإن الوقت الفاصل ما بين انتشار المحلول المخدر ومباشرة الجراحة كان ذا تأثير في الانتشار الشدقي – الحنكي للأرتيكائين %4 وذلك في عينات القلع التي استخدم فيها. A clinical trial was carried out to evaluate whether 4% articaine with epinephrine 1:100,000 deposited alone as a single buccal infiltration in impacted maxillary third molar removal provided sufficient palatal anesthesia as compared to routine buccal and palatal injection for the same surgical procedure. 90 teeth from 45 patients age 18 to 30 years were selected and enrolled in the present study. For the purpose of comparison, the sample was randomly divided into two main groups: Group I (trial group) which included 30 patients who were to receive single buccal injection for removal of 60 bilateral impacted maxillary third molars. While Group II (control group) included 15 patients who were to receive routine buccal and palatal injections for removal of 30 bilateral impacted maxillary third molars. Patients in group I were additionally divided into two subgroups: Subgroup (A) was anesthetized with 4% articaine with epinephrine1:100k and the extractions were initiated 6 minutes following anesthesia. Subgroup (B) used the same solution but 12 minutes was allowed for anesthetic spreading before the extraction .The following data were recorded: pain on needle insertion and deposition of solution, pain ratings experienced during surgery phases for both groups in numbers and percentages of extractions performed without and with the need for supplemental palatal anesthesia .The rate of sufficient buccal-palatal spreading as determined by the lack of necessity of additional palatal anesthesia was A (73.7%), B (90.2%). Most of the surgical extractions could be finished only with buccal anesthesia. However, time interval between deposition of the anesthetic solution and beginning of surgery did affect buccal–palatal spreading of 4% articaine in the extraction patterns used.